Mobile Learning Application for Enhancement of Teaching Tool in Java Programming - Azura Ahmad (Journal of Advanced Research in Computing and Applications, 2023)
Programming is a basic subject to several areas of technology. However, many students frequently faced a difficulty to understand the programming characteristic and visualize problem solution using programming. It is can help students improve their performance and attitude towards Java Programming Language. This method given hands-on experience and also learned through their experience. This paper study of mobile learning application used to help students improve their skill in Java Programming Language